Neoadjuvant chemotherapy before radical prostatectomy for locally advanced prostate cancer: Protocol for a systematic review and meta-analysis. Issue 35 (August 2019) - Lin, Tianhai; Yang, Xiong; Gong, Lina; Xu, Hang; Qiu, Shi; Yu, Ruichao; Sun, Sheng; Liu, Liangren; Zhang, Peng; Han, Ping; Cheng, Jingqiu; Yang, Lu; et al.
Abstract: Background: To evaluate the effectiveness and safety of neoadjuvant chemotherapy (NAC) for locally advance prostate patients undergoing radical prostatectomy. Methods: PubMed/Medline, EMBASE, Web of Science, Ovid, Web of Knowledge, and Cochrane Library will be searched for studies related to the topic. The identification, inclusion and exclusion flow charts will be conducted according to PRISMA guidelines. The identified reports will be critically appraised using GRADE approach. Bias and heterogeneity of included studies will be assessed, and outcome measurements from individual studies will be combined with 95% confidence interval using a fixed- or random-effects model if qualified. Results: This study will provide evidence and data on the tolerance and efficacy of NAC followed by radical prostatectomy (RP). Conclusion: The application of taxanes-based chemotherapy has been widened to metastatic hormone sensitive prostate cancer in recent years. To be more vigorous, whether neoadjuvant administration of these cytotoxic agents can improve the outcome of RP in locally advance prostate cancer patients has been explored. This study aims to synthesis data regarding the adverse effect, response rate, recurrence, and survival from multiple trials, and to guide the healthcare practitioners using an evidence-based approach.